2013
DOI: 10.1111/conl.12045
|View full text |Cite
|
Sign up to set email alerts
|

License to Kill: Reforming Federal Wildlife Control to Restore Biodiversity and Ecosystem Function

Abstract: For more than 100 years, the US government has conducted lethal control of native wildlife, to benefit livestock producers and to enhance game populations, especially in the western states. Since 2000, Wildlife Services (WS), an agency of the US Department of Agriculture, has killed 2 million native mammals, predominantly 20 species of carnivores, beavers, and several species of ground-dwelling squirrels, but also many nontarget species. Many are important species in their native ecosystems (e.g., ecosystem en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 44 publications
2
48
0
Order By: Relevance
“…The case supports recent suggestions from Ramp [8], Mehmet and Simmons [5] and Bergstrom et al [10] that a lack of transparency in coexistence decisions can lead to adverse outcomes for wildlife welfare. Behind the scenes the official correspondence emphasised human concerns for recreation safety and economic interests [3], and was dismissive of alternative solutions to culling, when compared to the subsequent public discourse in the media.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The case supports recent suggestions from Ramp [8], Mehmet and Simmons [5] and Bergstrom et al [10] that a lack of transparency in coexistence decisions can lead to adverse outcomes for wildlife welfare. Behind the scenes the official correspondence emphasised human concerns for recreation safety and economic interests [3], and was dismissive of alternative solutions to culling, when compared to the subsequent public discourse in the media.…”
Section: Discussionsupporting
confidence: 86%
“…Researchers have reported that the values of the wider public and government agencies responsible for wildlife management are frequently quite different [9] and that the views of large numbers of people are either ignored or not heard [10], raising the possibility that large numbers of animals are killed or otherwise harmed in ways that would not be approved by the citizens that decision-makers are representing. Studies in Canada reported that the public and experts agreed on potential harm levels, but management strategies that involved killing animals often lacked broad public support [11].…”
Section: Culling Justifications and Calls For More Transparencymentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, non-lethal interventions are often more effective in reducing livestock predation (Bergstrom et al 2014), and socially accepted methods like diversionary feeding need more attention. Within the management coexistence strand, the anger around compensation schemes may be harder to resolve when they are governed by perceived ''weak'' institutions (Ferraro and Kiss 2002) that favour an unfair distribution of payments (Hemson et al 2009).…”
Section: Managing Coexistence In Southern Transylvaniamentioning
confidence: 99%
“…In a case of widespread convergent evolution, examples of conservation initiatives aimed at achieving both conservation goals and reduced harm to individuals have emerged over the last few decades. Despite the dominant lethal paradigm underlying many conservation initiatives (Bergstrom et al 2014), compassionate approaches to solving conflicts between humans and wildlife have evolved. These highlight the rise of what has been termed 'compassionate conservation' (Bekoff 2010(Bekoff , 2013), a rapidly growing international and cross--disciplinary movement that stipulates that we need a conservation ethic that incorporates the protection of other animals as individuals: not just as members of populations of species, but valued in their own right.…”
Section: Compassion In Conservationmentioning
confidence: 99%